Transabdominal Pre-Peritoneal (TAPP) Laparoscopic Inguinal Hernia Repair: Our Experience with 40 Cases (Journal of Surgical Sciences, 2020)
Background: Groin hernias are the most common surgical conditions all over the world. Laparoscopic (TAPP) approach has been achieved as the best technique of inguinal hernia repair due to less postoperative pain, earlier return to activity and fewer wound complications.Objectives: To share our experience with Transabdominal preperitoneal (TAPP) hernia repair and its outcome.Methods: This prospective study was performed in Shaheed Suhrawardy Medical College Hospital between January 2016 to December 2017. Forty male patients with inguinal hernia were included in this study. Data was collected in a proforma regarding demographic and baseline characteristics, operative time, outcome of patients and were analyzed in tabulated form.Results: Total 40 patients were included in our study. Age ranged from 20-60 years (mean age ± SD 38.88±10.92 years). The maximum duration of TAPP hernia repair ranged from 100-120 minutes s(mean ± SD 109±16.3 minutes). Post-operative complications were severe pain (10%), infection (5%), scrotal oedema (5%).Conclusion: Laparoscopic TAPP hernia repair is associated with satisfactory short- and long-term results.Journal of Surgical Sciences (2020) Vol. 24 (1) : 11-14